Pengaruh Kompetensi Guru dan Supervisi Akademik Kepala Sekolah terhadap Kinerja Guru Kompetensi Keahlian Akuntansi dan Keuangan Lembaga di SMK Kabupaten Jepara - Wibawani, Esti; YSH, A.Y. Soegeng; Maryanto, Maryanto (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Teacher performance can be interpreted as a teacher who can carry out his duties professionally. As professional staff, teachers must be able to manage the learning process from the planning, implementation and evaluation stages. The aim of this research is to: determine the magnitude of the influence of teacher competence and academic supervision on teacher performance. The research approach used is quantitative. This type of research uses correlation research. The population of this study was 84 teachers and the research sample was 69 teachers. Data collection was carried out using a questionnaire. The research results show that: 1) The influence of teacher competence partially has a significant effect on teacher performance variables by 69.8%. 2) The influence of academic supervision partially has a significant effect on teacher performance variables by 72.9%. 3) The significant influence of teacher competency and academic supervision on teacher performance is 74.0%. The author suggests that school principals can reflect and evaluate by increasing the intensity of supervision. School principals can provide motivation and coaching to encourage teachers to complete their work well and be results-oriented so that they can improve teacher performance. Keywords: teacher performance, academic supervision, teacher competency